Der Einfluss der Abgeltungssteuer auf die Vorteilhaftigkeit von Anlagen in Genussscheine und Aktien - Halberstadt, Alexander; Sureth-Sloane, Caren; Voß, Armin (Die Wirtschaftsprüfung)

Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren

Umsatzsteuerausfall und Umsatzsteuerbetrug - Eine steuerökonomische Analyse der Umsatzsteuerdeklaration - Nordhoff, Daniel

Strukturprobleme angehen - Nordhoff, Daniel; Popp, Matthias (Niedersächsische Wirtschaft)

Verschärfung der Verlustabzugsbeschränkung durch § 8c KStG und deren Einfluss auf den Erwerb von Anteilen an Kapitalgesellschaften - Sureth-Sloane, Caren; Vollert, Pia

Investment Effects of Capital Gains Taxation under Simultaneous Investment and Abandonment Flexibility - Niemann, Rainer; Sureth-Sloane, Caren (Festzeitschrift für Franz W. Wagner: Accounting, Taxation, and Corporate Governance)

Information disclosure by answers to XPath queries - Böttcher, Stefan; Hartel, Rita (Journal of Computer Security)

Efficient construction of multiple geometrical alignments for the comparison of protein binding sites - Fober, T.; Klebe, G.; Hüllermeier, Eyke (in Proceedings ISDA-2009, 9th international Conference on Intelligent Systems Design and Applications, Pisa, Italy)

CSC: Supporting Queries on Compressed Cached XML - Böttcher, Stefan; Hartel, Rita (Database Technologies 2009, Twentieth Australasian Database Conference, ADC 2009)

XML Stream Data Reduction by Shared KST Signatures - Böttcher, Stefan; Hartel, Rita; Messinger, Christian (2009 42nd Hawaii International Conference on System Sciences)

Similarity analysis of protein binding sites: A generalization of the maximum common subgraph measure based on quasi-clique detection - Boukhris, I.; Elouedi, Z.; Fober, T.; Mernberger, M.; Hüllermeier, Eyke (In Proceedings IDA-2009, 9th International Symposium on Intelligent Data Analysis, Pisa / Italy)

Fuzzy modeling of labeled point cloud superposition for the comparison of protein binding sites - Fober, T.; Hüllermeier, Eyke (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

A fuzzy variant of the Rand index for comparing clustering structures - Hüllermeier, Eyke; Rifqi, M. (in Proceedings IFSA / EUSFLAT-2009 World Congress of the Fuzzy Systems Association, Lissabon, Portugal)

Methoden und Werkzeuge für einen effizienten Ultraschallsensorentwurf - Henning, Bernd

Trends in ultrasonic transducer design - Henning, Bernd
Ultrasonic sensors are widespread in the process industry for example to measure flow, filling level, density or substance concentration in liquid mixtures today. On one side technically high demands are made to the ultrasonic sensors on the other side the production of the ultrasonic sensors has to be more and more cost-efficient. Today, these two contrary demands only can be met by the use of efficient development tools. This contribution describes the state of technology in the field of the computer-assisted ultrasonic transducer development, however, also shows the limits.

Ultrasonic Sensors for Process Applications - Sensor Design - Henning, Bernd; Rautenberg, Jens; Schröder, Andreas; Unverzagt, Carsten (Proceedings Sensor 2009)
Today, ultrasonic sensor systems are often applied in process technology. For the opening up of new industrial fields of application, such as the non-invasive process tomography, ultrasound sensors are necessary which are stable and adapted optimally under process conditions. Only with such optimized ultrasonic sensors the functionality of the sensor systems can be enlarged decisively with support of a complex measurement data evaluation. This contribution deals especially with the design process.

Computer assisted design of transducers for ultrasonic sensor systems - Henning, Bernd; Rautenberg, Jens; Unverzagt, Carsten; Schröder, Andreas; Olfert, Sergei (Journal of Measurement Science and Technology, MST)
In this contribution, possibilities and methods for computer-assisted design of ultrasound transducers are described. These transducers are essential for an ultrasonic sensor design, e.g. for continuous non-invasive determination of quantities that are important in process technology. To achieve technical reliability and robustness, the precise determination of all acoustic properties of the used sensor materials is of great importance. Problem-oriented modeling, numerical simulation, special optimization algorithms and improved methods for the visualization of propagating waves offer new and promising possibilities for developing ultrasonic transducers with enhanced properties.

Generating of short ultrasonic pulses using active damping - Rautenberg, Jens; Olfert, Sergei; Henning, Bernd
In non-destructive testing (NDT) with ultrasound the emission of short pulses is essentially if the echoes of nearby obstacles should be separated from the emitted signal. In this contribution a new approach is shown how to gene-rate a short ultrasonic pulse using a 3$-$1 composite transdu-cer. Therefore the ceramic bars, which are embedded in a polymer matrix, will be regarded as an exciter for the entire structure. After the pulse excitation the same bars can also be used for active damping to increase the bandwidth of the entire system. The Mason model serves as a basis for the de-scription of the ultrasonic transducer and is extended to the composite structure. The excitation signal is adaptively mo-dified by a suitable signal processing. Therefore the changes of boundary conditions, like the ambient temperature or acoustic impedance of adjacent media are considered.

Interdisciplinary Collaboration in a Visualization Course - Domik, Gitta (Informatics Education Europe IV, November)

Einsatz von Simulationswerkzeugen in der Entwicklungskette von ultrahochfesten warmgeformten Strukturkomponenten im Fahrzeugleichtbau* - Böke, Johannes; Erhardt, Rüdiger; Rostek, Wilfried; Tröster, Thomas (Materials Testing)